Kajian Konsentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Jagung Manis (Zeamays L): Study of the Concentration Liquid Organic Fertilizer on The Growth and Yield of Sweet Corn (Zea mays saccarata L.) - muryanto; Priyono; Siswadi (Planta Simbiosa, 2023)
Corn (Zea mays saccarata L.) is one of the food crops that has strategic value, the need for sweet corn in Indonesia continues to increase along with the increasing population and its use as a processed product. This study aims to compare the effect of Rabbit LOF, Goat LOF, and Cow LOF applications on sweet corn plants (Zea mays saccarata L). The method used was a single-factor Randomized Complete Group Design (RCBD), there were 10 experimental units, each experimental unit was repeated 3 (three) times. This study used the following treatments: without control treatment (K0), dose of Rabbit LOF 40 ml/L water (K1), Rabbit LOF 40 ml/L water (K2), Rabbit POC 60 ml/L water (K3), Goat POC 20 ml/L water (K4), Goat LOF 40 ml/L water (K5), Goat LOF 60 ml/L water (K6), Cow LOF 25 ml/L water (K7), Cow LOF 50 ml/L water (K8), Cow LOF 75 ml/L water (K9). Observation data were analyzed using ANOVA and continued using BNT test at 1% level. The results showed that giving the concentration of 20 ml/L LOF Rabbit gave the best results on the weight parameter of the cob weight of 256, 17 g/plant or 25, 62 tons/ha.